2018
DOI: 10.17221/655/2018-pse
|View full text |Cite
|
Sign up to set email alerts
|

Use of biologically active substances in hops

Abstract: In four-year experiments, hop was treated with 7 biologically active substances in two terms during vegetation: Lignohumate max (a mixture of humic acids and fulvic acids), Lexin (a mixture of humic acids and fulvic acids enriched with auxins), Lexenzym (a mixture of humic acids and fulvic acids enriched with auxins, phytohormones and enzymes precursors), Ascophyllum nodosum seaweed extract, synthetic auxin, humic acids and fulvic acids alone. The chlorophyll content was monitored after the application both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Finally, it is worth mentioning that, despite the growing interest towards the application of plant biostimulants in other crops, studies conducted on this topic are very few for hops and no one in the Mediterranean Basin. In a recent study, Prochazka et al (2018) [93] found that complex formulations of biologically active substances, such as fulvic and humic acids and phytohormones, appear to be highly effective for the optimization of hop production performance in Czech Republic.…”
Section: Irrigation and Fertilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is worth mentioning that, despite the growing interest towards the application of plant biostimulants in other crops, studies conducted on this topic are very few for hops and no one in the Mediterranean Basin. In a recent study, Prochazka et al (2018) [93] found that complex formulations of biologically active substances, such as fulvic and humic acids and phytohormones, appear to be highly effective for the optimization of hop production performance in Czech Republic.…”
Section: Irrigation and Fertilizationmentioning
confidence: 99%
“…The restricted availability of plant protection products registered for hops severely limits the strategies for pest and disease control in both organic and conventional farming. Thus, hop protection management must focus on the proper agronomic practices, preventive intervention and biostimulants for induction of plant resistance [93]. These products determine a higher resistance of plant tissues (e.g., vaterite) and a higher synthesis of phytoalexins.…”
Section: Disease Pest and Weed Controlmentioning
confidence: 99%
“…The following biologically active compounds were used in the experiment: -Lignohumate B is a mixture of humic acids produced in the process of organic transformation from waste wood with the ratio of humic and fulvic acids 1: 1 (Procházka et al 2018); -Lexin is a concentrated solution of humic acids, fulvic acids, and auxins supporting plant cell division and elongation. Improving influence on root formation and growth and increase of yield was observed (Adamčík et al 2016); -Brassinosteroids are a relatively new group of steroid phytohormones from the terpenic family.…”
Section: Methodsmentioning
confidence: 99%
“…Seaweed algae extracts are complex products, containing plant hormones, brassinosteroids, betaines, polyamines, polymers and also macro and micronutrients [11]. Although the complexity of their composition tends to make it difficult to clarify their mode of action [6,9,12], several studies have shown beneficial effects from the use of seaweed extracts for the alleviation of abiotic [13][14][15] and biotic [16,17] stresses, and in increasing crop productivity and/or product quality [18][19][20], even if they provide minute quantities of nutrients [5].…”
Section: Introductionmentioning
confidence: 99%